2007
DOI: 10.1097/01.sle.0000213752.23396.45
|View full text |Cite
|
Sign up to set email alerts
|

Early Laparoscopic Cholecystectomy for Acute Gangrenous Cholecystitis

Abstract: Treatment of severe acute cholecystitis by laparoscopic cholecystectomy remains controversial because of technical difficulties and high rates of complications and conversion to open cholecystectomy. We investigated whether early laparoscopic cholecystectomy is appropriate for acute gangrenous cholecystitis. Pathologic diagnoses and outcomes were analyzed in patients who underwent laparoscopic or open cholecystectomy at our hospital, January 2002 to September 2005. Of 30 patients with acute gangrenous cholecys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…7,13,16,22 In our present cases, postoperative stay was similar or shorter than other reports; 3.7 days in group 2. In group 2, there was significant correlation among postoperative stay, age, and ASA class.…”
Section: Asa Classcontrasting
confidence: 47%
See 1 more Smart Citation
“…7,13,16,22 In our present cases, postoperative stay was similar or shorter than other reports; 3.7 days in group 2. In group 2, there was significant correlation among postoperative stay, age, and ASA class.…”
Section: Asa Classcontrasting
confidence: 47%
“…However, technical advances and increased experience have gradually led surgeons to attempt laparoscopic surgery in cases of acute gangrenous cholecystitis. 7,15,16 Tsushimi et al 22 reported that there were no postoperative complications. Thus, early laparoscopic cholecystectomy seems to be appropriate for acute gangrenous cholecystitis.…”
Section: Asa Classmentioning
confidence: 99%
“…[15][16][17][18] In our study, LCs in group 1 were performed at a mean of 6.1 days (range, 0 to 18 d) after admission. Tsushimi et al 25 reported appropriateness of early LC for acute gangrenous cholecystitis with a relatively high conversion rate (20.0%). However, there are no previous large-scale studies on LC for complicated severe acute cholecystitis according to the timing of the LC.…”
Section: Discussionmentioning
confidence: 98%
“…We believe that a low threshold for conversion is important to minimize the risk of major complications. [11] 6/44 (13.6%) 18/24 (75%) Kum [16] 7/54 (13%) Cox [17] 33/98 (33.7%) 21.8% 50% 83.3% Bingener [18] 33/97 (34%) Habib [19] 14/44 (32%) Suter [20] 15.6% Tsushimi [21] 4/20 (20%) Araujo-Teixeira [22] 24/100 (24%) Koperna [23] 44 Lo et al [13] advocated an early decision for conversion of LC to open procedure for the treatment of AC. We consider that the surgeon should never hesitate to convert, should make an early decision for it within 15 to 20 min on average, and not persist with a difficult dissection.…”
Section: Discussionmentioning
confidence: 99%